Opting Out of Standardized Tests at the Secondary Level-A Geographic Analysis of Colorado - Lydia Ross; Kathryn P. Chapman; Sherman Dorn; Carlos R. Casanova (SAGE Publishing, 2023)
Although much of the national opt-out movement is parent driven, the Colorado opt-out movement involved considerable efforts from high school students. This study explores the geography of the Colorado opt-out movement among secondary students, drawing upon social movements theory. We utilize the Colorado Measures of Academic Success (CMAS) as a measure of opt-out behavior in Colorado between 2016-2019. We also examine school-level demographic data. We first applied ordinary least squares regression and then utilize multiscale geographically weighted regression (MGWR) to examine the relationships between school-level demographics and opting out behavior for 11th-grade standardized assessments in Colorado. This analysis demonstrates the importance of geography in enacting social networks surrounding the opt-out movement in the state of Colorado. This study offers insight into opting out in the unique context of youth activism in Colorado, with a specific focus on geographical analysis.